Curious George - Rey, H. A. 1898-1977. (Hans Augusto) (Boston : Houghton Mifflin, 1941)
Curious George has many misadventures after the man with the yellow hat takes him across the sea.
Keywords: Curious George (Fictitious character) -- Juvenile fiction; Monkeys -- Juvenile fiction; Curious George (Fictitious character) -- Fiction; Monkeys -- Fiction